2010
DOI: 10.1002/zaac.201000108
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Transition Metal Acetylides AI2M0C2 (AI = K, Rb; M0 = Pd, Pt): Neutron Diffraction Studies and Electronic Properties 

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The (001) surface energies also indicate a much stronger Pd-C bond than Te-C one. While there is a σ-bond in both Pd-C and Te-C links between the 2sp 1 hybrid orbital of the C atom and the 5sp 1 hybrids of Pd and Te (all oriented along the M-C-C line) the Pd-C link is further strengthened by strong back-donation of Pd 4d shell electrons to the antibonding π-orbitals of the C 2− 2 ions, also associated with lengthening of the C-C bond 5 . Also note that Cs 2 Te (and also Cs 2 TeC 2 ) has the advantage over the formerly mentioned multi-alkali-antimonides that Cs is better bound in them allowing for longer operational lifetime 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The (001) surface energies also indicate a much stronger Pd-C bond than Te-C one. While there is a σ-bond in both Pd-C and Te-C links between the 2sp 1 hybrid orbital of the C atom and the 5sp 1 hybrids of Pd and Te (all oriented along the M-C-C line) the Pd-C link is further strengthened by strong back-donation of Pd 4d shell electrons to the antibonding π-orbitals of the C 2− 2 ions, also associated with lengthening of the C-C bond 5 . Also note that Cs 2 Te (and also Cs 2 TeC 2 ) has the advantage over the formerly mentioned multi-alkali-antimonides that Cs is better bound in them allowing for longer operational lifetime 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We mainly achieved two series of compounds with the general compositions A I M I C 2 with A I =Li–Cs and M I =Cu, Ag, Au and A I 2 M 0 C 2 with A I =Na–Cs and M 0 =Pd, Pt . The latter are semiconductors with small indirect band gaps, whose sizes depend on the nature of the respective alkali metal ion A + . Very recently, these compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values making them interesting candidates for possible applications as photocathodes and novel intercalation electrode materials for batteries .…”
Section: Figurementioning
confidence: 99%
“…[8] But despite some very spectacular results [9] their work was hampered by the fact that crystal structure elucidation from powder diffraction turned out to be impossible in most cases and that the handling of many of the investigated compounds was difficult due to their highly explosive nature.I tw as again our group that was able to present the first crystal structures of ternary alkali metal transition metal acetylides containing C 2 2À anions. [15] Very recently,t hese compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values [16] making them interesting candidates for possible applications as photocathodes [17] and novel intercalation electrode materials for batteries. [14] The latter are semiconductors with small indirect band gaps, whose sizes depend on the nature of the respective alkali metal ion A + .…”
mentioning
confidence: 99%
“…[14] The latter are semiconductors with small indirect band gaps, whose sizes depend on the nature of the respective alkali metal ion A + . [15] Very recently,t hese compounds have attracted some attention, as based on DFT calculations it was concluded that they should exhibit an anomalous anisotropy of workfunction values [16] making them interesting candidates for possible applications as photocathodes [17] and novel intercalation electrode materials for batteries. [18] Even better workfunction values were calculated for ap otential Cs 2 Te C 2 compound, which was assumed to crystallize in the Na 2 PdC 2 structure type with linear ···Te-C C-Te··· chains in these calculations.…”
mentioning
confidence: 99%